Acupuncture for Pain Control after Caesarean Section: A Prospective Observational Pilot Study. Issue 1 (February 2016) - Hesse, Thomas; Henkel, Berthold; Zygmunt, Marek; Mustea, Alexander; Usichenko, Taras I
Objective: Options for pharmacological analgesia in patients who have undergone Caesarean section (CS) are often restricted. Acupuncture is a promising tool for treating postoperative pain. We aimed to study the feasibility and acceptability of acupuncture as an additional method of analgesia in CS patients in a prospective observational pilot investigation. Methods: Twenty-two patients scheduled for elective CS under spinal anaesthesia were enrolled according to set inclusion criteria. Each patient received auricular and body acupuncture with 20 indwelling fixed needles according to previously validated protocols of acupuncture for postoperative analgesia. Pain intensity on an 11-point verbal rating scale (VRS-11, where 0=no pain and 10=maximal pain), analgesia-related side effects, time to mobilisation and Foley catheter removal after CS, and patients' compliance and satisfaction with treatment of pain on a 5-point VRS (VRS-5, where 1=excellent; 5=bad) were recorded. Results: Twenty patients were included in the final analysis. One patient was disturbed by paraesthesia at the site of needling. All other patients tolerated acupuncture well. Pain intensity on movement on the first postoperative day was 4.3±2.4 (mean±SD; VRS-11) and decreased to 2.2±1.2 on the day of discharge. Patient satisfaction was 1.9±0.8 (mean±SD; VRS-5) and compliance (rated by their nurses) was 1.5±0.5 (mean±SD; VRS-5). Conclusions: Acupuncture for additional analgesia after CS was well accepted. The primary outcome measurement was feasible and allowed the sample size to be calculated for a future randomised controlled trial.